APPLICATION OF ARECA NUT EXTRACT AS A NATURAL COLORANT IN THE PROCESS OF IN ECO-FRIENDLY SOAP MAKING - Malse Anggia; Ruri Wijayanti; Ariyetti (JURNAL KATALISATOR, 2024)
The use of synthetic dyes can be harmful to health. While natural dyes are non-toxic, easily degradable and environmentally friendly. Areca nut extract contains tannins and anthocyanins, which are natural pigments that have potential as natural dyes. Natural coloring from areca nut extract is applied to solid soap. Areca seeds are extracted and then dried with three different drying methods, namely the oven, dehydrator and Freeze dryer methods to produce powdered dyes. Different drying of areca nut extracts will produce areca nut extracts with different chemical content. This study aims to determine the results of chemical analysis of soap added with areca nut extract with several different drying methods and determine the best formulation of soap added with areca nut extract and SNI test of solid soap produced by using areca nut extract powder. The research method used is experimental laboratory. The analysis of solid soap preparations carried out includes pH test, water content, foam power and organoleptic test. The research results were processed using descriptive analysis. The results showed that the pH of solid soap added with areca nut extract with different drying met the SNI requirements. The water content of areca nut extract solid soap meets SNI requirements, which is no more than 15%. And based on the results of the liking of solid soap according to the organoleptic results of areca nut extract soap with the treatment of drying areca nut extract with dehydrator formula 2 produces areca nut extract solid soap that is most liked by panelists.